Evaluation of e-vermicompost for tomato production - Haque, MA; Khan, MR; Akram, S (Bangladesh Journal of Nuclear Agriculture, 2023)
Vermicompost has a plethora of benefits that restores nutrient, stabilizes soil, and enhances soil fertility. The experiment was conducted at farmers’ field of Mymensingh and Jamalpur to evaluate the effect of e-vermicompost on tomato production during October 2019 to March 2020. There were five fertilizer treatments combination (T1: RCF-Recommended fertilizer (N120 P35 K70 S15 Zn2 B0.5), T2: 85 % RCF+3 t ha-1 vermicompost, T3: 85% RCF+1 t ha-1 e-vermicompost, T4: 70% RCF+3 t ha-1 e-vermicompost and T5: 70% RCF+1 t ha-1 e-vermicompost). The experiment was laid out in a Randomized Complete Block Design with three replications. The fresh tomato fruits were harvested in three times. The fresh weight of tomato at Mymensingh ranged from 53.3 to 68.5 t ha-1 with the highest yield of 68.5 t ha-1 from the treatment T2 (85% RCF + 3 t ha-1 e-vermicompost). At Jamalpur, the yield ranged from 50.4 to 65.3 t ha-1 and the highest yield of 65.3 t ha-1 was recorded also from the treatment T2 (85% RCF+3 t ha-1 e-vermicompost). The lowest yield was obtained from the treatment T5 in both locations. The percent fresh yield increased over control (T1), was 24.5 and 18.3% in Mymensingh and Jamalpur, respectively. The highest gross margin was Tk. 762,225/-, which was obtained from the treatment T2 (85% RCF+3 t ha-1 e-vermicompost). The highest MBCR 2.80 (average of two locations) was obtained from the same treatment T2 (85% RCF+1 t ha-1 e-vermicompost). The results indicates that the application of e-vermicompost along with 85% recommended dose of chemical fertilizer is more profitable than the application of chemical fertilizer alone. Bangladesh J. Nuclear Agric, 37(1): 31-40, 2023